Meningkatkan Literasi Numerasi Melalui Pembelajaran Berbasis Masalah Berkonteks Islam dengan Berbantuan Geogebra - Purnomo, Suryo (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2024)
This research aims to implement a context-based problem-solving learning model with Islamic context assisted by GeoGebra to enhance the numeracy literacy skills of students in the topic of matrix in Grade XI MIPA at MAN Barito Timur. The study employs a classroom action research approach with two cycles. Data is collected through pretests, post-tests, observations of learning implementation, and student worksheets. The results indicate that applying the learning model successfully improves students' numeracy literacy skills. In cycle 1, there was an increase from 5 students reaching the minimum passing grade (KKM) in the pretest to 9 students or 56% in the post-test. In cycle 2, 7 students achieved KKM in the pretest, which increased to 12 students in the post-test, reaching 75%. Student engagement also improved positively, reflecting the effectiveness of the learning model. The use of GeoGebra as a tool for visualization and exploration had a positive impact on deeper understanding. In conclusion, the Islamic context-based problem-solving learning model assisted by GeoGebra effectively enhances students' numeracy literacy. Keywords: problem-based learning, numeracy literacy, Islamic context, GeoGebra